2019
DOI: 10.2298/abs190705045r
|View full text |Cite
|
Sign up to set email alerts
|

Different responses to environmental factors in terpene composition of Pinus heldreichii and P. peuce: Ecological and chemotaxonomic considerations

Abstract: Many studies show the influence of the environment on terpene composition, but not many of them deal with the terpene composition variability in correlation with environmental factors in Pinus. We chose two endemic species-P. heldreichii Christ. (Bosnian pine) and P. peuce Griseb. (Macedonian pine)-two relict and (sub)endemic species of the Balkan peninsula. They mainly form pure stands but can appear in mixed populations, most commonly with each other. These species belong to different subgenera and thus diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
1
10
4
Order By: Relevance
“…The sand percentage in soil and the average annual temperature (averaged analysis) and the maximum wind intensity (focused analysis) were those identified as to possibly influence the RAc profiles. These results are consistent with previous comparable CCA studies on pine forests, where the average annual temperature was suggested to influence the resin acid profile ( Arrabal et al., 2005 ; Rajčević et al., 2019 ). The occurrence of cavitation due to strong winds has been suggested to influence oleoresin production ( Ioannidis et al., 2019 ); however, the time-constrained CCA suggests a putative correlation of the wind intensity with the resin acid profiles as well.…”
Section: Discussionsupporting
confidence: 93%
“…The sand percentage in soil and the average annual temperature (averaged analysis) and the maximum wind intensity (focused analysis) were those identified as to possibly influence the RAc profiles. These results are consistent with previous comparable CCA studies on pine forests, where the average annual temperature was suggested to influence the resin acid profile ( Arrabal et al., 2005 ; Rajčević et al., 2019 ). The occurrence of cavitation due to strong winds has been suggested to influence oleoresin production ( Ioannidis et al., 2019 ); however, the time-constrained CCA suggests a putative correlation of the wind intensity with the resin acid profiles as well.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that the resin characteristics evaluated are not directly related to the joint variation of geographic and climatic factors. This may indicate that the variation in primary components and resin quality may be due to genetic factors [26]) or phenotypic characteristics of the trees [15]. Even other variables such as soil type, geological substrate and exposure can influence resin characteristics such as yield and chemical components [11,26].…”
Section: Provenance Clusteringmentioning
confidence: 99%
“…and P. merkusii, P. silvestris L. and P. peuce Griseb. [19,[24][25][26]. For Mexican pine species and in particular for P. oocarpa, the relationship between resin characteristics with geographic and climatic variables has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Pinus heldreichii (Bosnian pine) has been used in traditional medicine in the middle, south, and west Bosnia and Herzegovina to treat pulmonary ailments (Šarić Kundalić et al, 2010). Pinus heldreichii mainly form pure stands but can appear in mixed populations, most commonly with Pinus peuce -Macedonian pine (Rajčević et al, 2019). The essential oils of P. heldreichii showed inhibitory action against respiratory pathogenic bacterial strains isolated from human swabs (Mitić et al, 2019).…”
Section: Pinus Sylvestris and Other Pinus Speciesmentioning
confidence: 99%